2022
DOI: 10.1145/3534580
|View full text |Cite
|
Sign up to set email alerts
|

Template Matching Based Early Exit CNN for Energy-efficient Myocardial Infarction Detection on Low-power Wearable Devices

Abstract: Myocardial Infarction (MI), also known as heart attack, is a life-threatening form of heart disease that is a leading cause of death worldwide. Its recurrent and silent nature emphasizes the need for continuous monitoring through wearable devices. The wearable device solutions should provide adequate performance while being resource-constrained in terms of power and memory. This paper proposes an MI detection methodology using a Convolutional Neural Network (CNN) that outperforms the state-of-the-art works on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
4
1
Order By: Relevance
“…Although exhibiting a slightly lower accuracy (94.76%) compared to the solution delineated in reference [27] (95.22%), this work approach distinguished itself by minimizing computational complexity, rendering it suitable for resource-constrained wearable devices. In contrast, reference [24] outperformed our method in wearable device memory occupancy, requiring only 20 kB, even if there was a diminished accuracy (84.36%) in comparison to this study's solution. Lastly, compared to the study presented in [30], which employed a deep LSTM network, our work demonstrated superior performance in terms of accuracy (84.17%) and feasibility for wearable devices in real-time MI detection.…”
Section: Methods 2: Performance Analysiscontrasting
confidence: 71%
See 3 more Smart Citations
“…Although exhibiting a slightly lower accuracy (94.76%) compared to the solution delineated in reference [27] (95.22%), this work approach distinguished itself by minimizing computational complexity, rendering it suitable for resource-constrained wearable devices. In contrast, reference [24] outperformed our method in wearable device memory occupancy, requiring only 20 kB, even if there was a diminished accuracy (84.36%) in comparison to this study's solution. Lastly, compared to the study presented in [30], which employed a deep LSTM network, our work demonstrated superior performance in terms of accuracy (84.17%) and feasibility for wearable devices in real-time MI detection.…”
Section: Methods 2: Performance Analysiscontrasting
confidence: 71%
“…The NN operated correctly, with the NN pulse being invoked every 6 s, taking 830 ms for Spectrogram calculation and inference, in line with the algorithm outlined in the block diagram of Figure 6. The literature contributions that adopted a comparable approach to Method 2 were those using II-lead ECGs, i.e., [24,27,30]. Limited studies in the literature have utilized experiments based on II-lead ECGs, with detailed performance comparisons illustrated in Table 11.…”
Section: Methods 2: Performance Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Further, SELF-CARE could be applied more broadly in the domain of affective computing to include additional tasks beyond stress detection and emotion recognition. Moreover, it can also be applied to other wearable healthcare applications like human activity recognition [29]- [31], myocardial infarction detection [32]- [34] etc., that involves data from multiple wearable sensors. Lastly, SELF-CARE's use of a specialized set of ensemble classifiers has broad applicability to IoT sensing, including the domains of sensor networks [35], and transportation [36].…”
Section: Limitations and Future Directionsmentioning
confidence: 99%